Black Stone Mining (Effort to Control Environmental Damage) - Zulkifli H. Demanto Demanto (Universitas Negeri Gorontalo, 2022)
This study discusses black stone mining in Bone Bolango Regency, Gorontalo Province. The type of research used in this research is sociological or empirical legal research. This research uses a normative legal science approach (laws and regulations). The author finds that the legal consequences arising from the illegal mining of black stone in Bone Bolango Regency is a criminal act in the mining sector prohibited by regulations, and the authors find that the role of the District Government. Bone Bolango in preventing environmental damage due to black stone mining activities consists of 3 things, namely; 1). Reclamation; 2). Periodic checking and monitoring; 3). Providing education to the community. Based on the explanation in the discussion and conclusions that the authors have described above, the authors have recommendations for suggestions to the government as follows; 1). Local governments must actively participate in protecting the environment in cases of damage caused by illegal mining activities; 2). The government must formulate appropriate regulations to protect the rights and interests of all parties.